Visualisasi Data Perkara Tindak Pidana Umum Menggunakan Python (Studi Kasus : Case Management System Kejaksaan Negeri Labuhanbatu Tahun 2023-2024) - Adryan, Ahmad; Andre, Ivo; Rambe, Fani Wulandari; Sitorus, Sahat Parulian (Universitas Labuhanbatu, 2026)
This study examines general criminal cases at the Kejaksaan Negeri Labuhanbatu for the years 2023–2024, focusing on three main aspects: case types, monthly trends, and the status of case handling. The data were analyzed and visualized using Python with pandas and matplotlib, producing bar and line charts that facilitate the identification of patterns, fluctuations, and case distribution. The analysis shows a decrease in Narcotics and Theft cases, while other case types, including Child Protection and Fraud, remained relatively stable. Monthly trends revealed that the highest number of cases occurred in November 2023, whereas the lowest was observed in April 2024, indicating potential seasonal effects on case occurrences. Regarding case handling, most cases successfully reached the stages of File Receipt and Complete File, although the number of cases achieving execution decreased compared to the previous year. These visualizations provide a clear and comprehensive view of the workflow from case initiation to execution, highlighting stages that require more attention and resources. Overall, this study demonstrates that data visualization can significantly improve understanding of complex datasets, support strategic planning, and assist the District Attorney’s Office in prioritizing case management for general criminal cases.